The egg and I - MacDonald, Betty Bard (Philadelphia J. B. Lippincott company, 1945)
Relates the joys and frustrations of life on a poultry farm in the mountains of Washington.
"A part of this book appeared in a condensed serialization in the Atlantic monthly."--Dust jakcet.
"First edition."
Keywords: Farm life